(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Patients with nephrotic syndrome (NS) are susceptible to different types of bacterial, viral & fungal infections. This prospective observational study was performed in the Pediatric Nephrology unit of Bangabandhu Sheikh Mujib Medical University, Dhaka from January, 2006 to May, 2008 to determine the types of infection associated with initial attack of idiopathic NS and to alert the physicians about this so that they can take preventive and therapeutic measures more promptly. 112 admitted children aged one to fifteen years with first attack of idiopathic NS were included. After control of existing infection, prednisolone was given in recommended dose & duration. All patients were followed for development of any type of new infection up to completion of treatment. Mean age was 61.87 months & male female ratio was 1.49:1. Most patients (78.57%) had been suffering from different types of infection on admission with male preponderence (59.09%) & most were under-6 years old (67.04%). During prednisolone therapy, 29.46% patients developed infections, 63.64% were male and under-6 years old were 72.73%. Fever, cough, abdominal pain & loose motion were the commonest presentations related to infection. Acute respiratory infection (ARI), acute watery diarrhea & urinary tract infection (UTI) were the most common infections on admission (53.57%, 34.82%, and 7.14% respectively). ARI & oral thrush were commonest infections during treatment with prednisolone (14.27% & 12.50% respectively). Infection should be ruled out carefully in every case of NS at each visit and during management in hospital & outside to reduce morbidity & mortality. Chattagram Maa-O-Shishu Hospital Medical College Journal Volume 12, Issue 3, September 2013: 1-4